Keeping CALM: When Distributed Consistency Is Easy: In distributed systems theory, CALM presents a result that delineates the frontier of the possible. - HELLERSTEIN, JOSEPH M.; ALVARO, PETER (Communications of the ACM, 2020)
The article discusses the theorem known as Consistency As Logical Monotonicity (CALM) as related to distributed big data systems in computing. It discusses the concept of confluence, provides a proof sketch, and the Bloom computer programming language.